Otimismo nas telas : a propaganda oficial da ditadura civil-militar nos cinejornais da agência nacional (1964-1979) - Freitas, Isadora Dutra de (2020)
The civil-military dictatorship maintained an extensive apparatus responsible for the production of its public image. Through official institutions, it produced and distributed informational content about the presidential routine, controlling the forms of representation of the regime. Thus, the main objective of this dissertation is to analyze how the State kept active this propaganda apparatus responsible for elaborating its self-image, having positive narratives and silencing sensitive aspects. To this end, we used as a documentary framework the newsreels produced by the National Agency, the main government information agency between the years 1964 and 1979. Through content analysis, we carried out the process of studying the sources in two stages, establishing the thematic focus through the quantitative survey and, subsequently, a qualitative analysis of the discourse in line with the images. These small newscasts, shown in movie theaters, had the function of informing the population about the main subjects of that week, emphasizing the presidential agenda, becoming an important propaganda tool. However, this strategy was not an innovation of the civil-military dictatorship. Newsreel was widely used as an expression of official discourse, mainly in the totalitarian regimes of Europe. In Brazil, it gained popularity during the "Estado Novo", a period in which a process of systematizing official propaganda began. During the dictatorship, these productions were again incorporated as a way of legitimizing the government. However, considering the context marked by censorship and practices of State terrorism, we courted our primary source with the opinion of critics and cinema experts published in the press. Therefore, it was possible to contemplate in greater depth the data that was omitted by the National Agency. Thus, through the analysis of the most recurring symbols and themes, we were able to affirm that these representations were based on the binomial Security and Development.